(untitled) (TAJ: Journal of Teachers Association, 2020)
Background: The highest prevalence rates of childhood obesity have been observed in developed countries, however, its prevalence is increasing in developing countries as well. Early detection of obesity and identification of risk factors are the key to successful prevention of obesity. Objectives: This study was conducted to determine the proportion of obesity and presence of risk factors in obese children in primary schools of Rajshahi city. Methodology: This cross sectional study included total 225 children chosen from different primary schools of Rajshahi city during the school year 2016-2017. Data collection tool used for the study was an interview schedule and this predesigned questionnaire. The main outcome measures were obesity and risk factors prevalent in the obese school children. Data were analyzed by SPSS version 20 and ‘Chi square’ test was applied for the test of significance. Result: Among the total 225 respondent, 121 (53.8%) were male, while 104 (46.2%) were females, with a mean age of 7.9 ±1.1 years. The mean and standard deviation of anthropometric measurement were weight 22.7±5.3 kg, height 120±8.1 cm and BMI 15.5±2.1 kg/m. Out of 225 participants, 2.7% (total 6) were overweight, 5.3% (total 12 students) were obese, 83.6% (total 188 students) were normal weight and 8.4% (total 19 students) were underweight. The rate of obesity was highest at the age of 8-9 years (10.7%) and overweight were highest at the age of 9-10 years (5.5%). Playing, biking regularly was strongly associated with fewer incidence of overweight and obesity (p value -.001). Faulty dietary habit, having more fast food, chocolate, sugary juice lead to a higher BMI and more fresh fruit and vegetables had lower BMI (p value .001). Conclusion: This study shows that childhood obesity is on rise in our country. Addressing the problem at its earliest could be achieved through identifying high risk groups and planning early intervention. Effective interventions and preventive strategies should be instituted at local and national level to reduce the incidence and comorbidities associated with obesity. TAJ 2020; 33(2): 39-45